3×71,5=214,5
4,6-3=1,6
1,6×4=6,4
214,5+6,4=220,9
126 - (42:6+1) = 126 - (7+1) = 126-8 = 118
Ответ:
Ответ 1 1923/2150
Пошаговое объяснение: 37/43-15/16=-53/688;
24/25* -53/688=-159/2150; 24/25 +37/43=1957/1075- -159/2150=4073/2150=1 1923/2150
Ответ:
0.75
Пошаговое объяснение:
Для начала переворачиваем дробь превращая деление в умножение:(x-3)*(x+3)/(x-3)^2 =(x-3)*(x+3) делим на (x-3)^2 сокращаем на х-3
= (x+3)/(x-3)=(-21+3)/(-21-3)=-18/-24=0.75
70*4=10*(7*4)=280
90*5=10*(9*5)=450
50*9=10*(5*9)=450
30*8=10*(3*8)=240
20*7=10*(2*7)=140
80*6=10*(8*6)=540